ISLAMIC AND RELIGIOUS STUDIES: Challenges and Opportunities for Twenty-First Century Indonesia (State Islamic University (UIN) of Sunan Ampel Surabaya, 2009)
This paper explores challenges and opportunities for Religious and Islamic Studies in the opening years of the twenty first century. It is especially concerned with relationships between the Indonesian, North American and Global contexts in which the two disciplines are located and the ways in which scholarly discourse can be enriched by trans-national cooperation and discourse. It is argued that Religious Studies should be understood as an academic discourse about religion and must be clearly distinguished from religious discourse internal to and across confessional lines. In a more concrete way, the paper is concerned with the epistemological foundations of the academic study of religion and with the issue of pluralism. It is argued that in today’s globalized world pluralism is a fact that cannot be ignored or eliminated. Discussion on what Eck has identified as three dimensions of pluralism, civic, theoloÂgical and academic.